2001
DOI: 10.1002/1529-0131(200111)44:11<2492::aid-art429>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging and miniarthroscopy of metacarpophalangeal joints: Sensitive detection of morphologic changes in rheumatoid arthritis

Abstract: Objective To evaluate and characterize magnetic resonance imaging (MRI) findings in the metacarpophalangeal (MCP) joints of rheumatoid arthritis (RA) patients macroscopically, using miniarthroscopy (MA; needle arthroscopy). Methods The second MCP joint of the dominant hand of 22 RA patients (13 with various RA activities/stages; 9 with early RA [≤1.5 years' duration]) was examined by MRI followed by MA. Findings were evaluated by standardized semiquantitative measures of synovial and bony pathologic changes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0
13

Year Published

2002
2002
2006
2006

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(91 citation statements)
references
References 55 publications
0
78
0
13
Order By: Relevance
“…Are erosions seen on MRI the same lesions as those detected by plain radiography? The answer to this question seems to be yes, in the main, as illustrated by studies comparing MRI findings with those of miniarthroscopy and ultrasound (25,26). However, cortical bone, which is so well-visualized on plain radiographs as a white line, appears on MRI as a low signal region that may be confused with focal (and potentially transient) subcortical bone marrow edema (11).…”
Section: Discussionmentioning
confidence: 99%
“…Are erosions seen on MRI the same lesions as those detected by plain radiography? The answer to this question seems to be yes, in the main, as illustrated by studies comparing MRI findings with those of miniarthroscopy and ultrasound (25,26). However, cortical bone, which is so well-visualized on plain radiographs as a white line, appears on MRI as a low signal region that may be confused with focal (and potentially transient) subcortical bone marrow edema (11).…”
Section: Discussionmentioning
confidence: 99%
“…Relevant research topics include examination of the occurrence of MRI bone erosions in other diseases and in healthy controls, development and validation of evaluation systems, and comparison with reliable references (e.g., histopathology, miniarthroscopy, and computed tomography). Although preliminary data obtained by ultrasonography-guided biopsies (15) and miniarthroscopy (16) indicated that MRI erosions represent true bone damage, more data are warranted. Large followup studies are needed to confirm the prognostic value of MRI bone erosions in early RA and in early persistent polyarthritis.…”
Section: Discussionmentioning
confidence: 99%
“…In all patients, 3 serial arthroscopically guided synovial biopsies of the same index joint, at baseline, after 4 weeks of treatment, and at the end of the treatment period at 12 weeks were performed under local anesthesia (29). The joints subjected to the arthroscopic biopsy procedure were the knee joint (n ϭ 7), wrist joint (n ϭ 2), ankle joint (n ϭ 1), and MCP joint (n ϭ 1) (30,31).…”
Section: Methodsmentioning
confidence: 99%